2015
DOI: 10.1021/acs.joc.5b01651
|View full text |Cite
|
Sign up to set email alerts
|

Dethreading of Tetraalkylsuccinamide-Based [2]Rotaxanes for Preparing Benzylic Amide Macrocycles

Abstract: The dethreading of a series of succinamide-based [2]rotaxanes bearing benzylic amide macrocycles is reported herein. These transformations proceeded quantitatively either under flash vacuum pyrolysis, conventional heating, or microwave irradiation. Studying the size complementarity of the stoppers at the ends of the thread and the cavity of the macrocycle allowed us to set up the best substituents for implementing the extrusion of the thread from the interlocked precursors. A variety of (1)H NMR kinetic experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 40 publications
0
46
0
Order By: Relevance
“…The macrocycles are comprised of two 1,4‐phenylene units that are connected by two isophthalamide units . The synthetic approach to prepare the [2]rotaxanes was carried out by a five‐component clipping methodology , , . Afterwards, a two‐step procedure was used for rotaxane synthesis: ( i ) synthesis of threads and ( ii ) interlocked molecules.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The macrocycles are comprised of two 1,4‐phenylene units that are connected by two isophthalamide units . The synthetic approach to prepare the [2]rotaxanes was carried out by a five‐component clipping methodology , , . Afterwards, a two‐step procedure was used for rotaxane synthesis: ( i ) synthesis of threads and ( ii ) interlocked molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Clegg et al demonstrated equilibria between rotamers in different solvents. Martinez‐Cuezva et al, reported the quantification of conformers by 1 H NMR analysis without the identification of each form and the reasons that influence the proportions. Leigh et al showed that [2]‐ and [3]catenanes move in discrete steps between different binding sites on the larger ring; this movement occurs with the change of conformers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Literature results show that an external stimulus can reduce the stability of pseudorotaxane (a rotaxane with one blocking group)/rotaxanes, promoting disassemblage. For example, Martinez-Cuezva et al promoted the dethreading of a [2]rotaxane using heat, flash vacuum pyrolysis, or microwave radiation [14]. Leung showed that reducing the interaction strength between axle and wheel via deprotonation or switch of solvent accelerated disassemblage [15].…”
Section: Introductionmentioning
confidence: 99%